2019
DOI: 10.1523/jneurosci.2687-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Hippocampal Actin Polymerization Is Necessary for Activation of G-Protein-Coupled Estrogen Receptor (GPER) to Increase CA1 Dendritic Spine Density and Enhance Memory Consolidation

Abstract: Activation of the membrane estrogen receptor G-protein-coupled estrogen receptor (GPER) in ovariectomized mice via the GPER agonist G-1 mimics the beneficial effects of 17␤-estradiol (E 2 ) on hippocampal CA1 spine density and memory consolidation, yet the cellsignaling mechanisms mediating these effects remain unclear. The present study examined the role of actin polymerization and c-Jun N-terminal kinase (JNK) phosphorylation in mediating effects of dorsal hippocampally infused G-1 on CA1 dendritic spine den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…1 ) [ 22 ▪ ]. GPERs are for example highly expressed in hippocampal neurons where they activate pathways involved in cognitive functioning [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 22 ▪ ]. GPERs are for example highly expressed in hippocampal neurons where they activate pathways involved in cognitive functioning [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of memory was not due to activation of the extracellular signal-regulated kinase signaling normally observed following E2 treatment. Rather, GPER activation was associated with phosphorylation of c-Jun N-terminal, cofilin-mediated actin polymerization, and spinogenesis in region CA1 (55,57). Overall, these studies provide strong evidence that like E2, activation of GPER can facilitate hippocampal-dependent memory performance.…”
Section: Role Of Gper In Hippocampal-dependent Spatial Memorymentioning
confidence: 69%
“…Interestingly, Oberlander and Woolley demonstrated that GPERinduced potentiation of excitatory synaptic responses in CA1 hippocampal pyramidal neurons is restricted to females and involves postsynaptic mechanisms (61). The role of GPER in synaptic plasticity is still evolving (62-65); however, a number of recent studies indicate that activation of GPER contributes to a rapid increase in hippocampal dendritic spinogenesis and spine density (11,54,57,60,61,66,67).…”
Section: Gper and Hippocampal Synaptic Functionmentioning
confidence: 99%
“…The cortical actin network is essential in the organization of neuronal compartments and plays a crucial role in membrane receptor movement ( Schevzov et al, 2012 ), thus we speculated that the cortical actin network may play a pivotal role in the effect of E2 on the receptor dynamics. Previous studies show that E2 induces cytoskeleton assembly mediated by GPER1 receptors via different intracellular signaling pathways, including the Rho-associated protein kinase (ROCK)-cofilin ( Gowrishankar et al, 2012 ; Wang et al, 2019 ) and c-Jun-N-terminal kinase (JNK)-cofilin ( Kim et al, 2019 ) pathways. To determine the possible role of cortical actin in the effects of E2 on glutamate receptors, we treated cells with the actin polymerization inhibitor, latrunculinA (latA; l μM).…”
Section: Resultsmentioning
confidence: 99%